A parallel arithmetic for hardware realization of digital filters. (January 2019) - Fan, Chunxiao; Li, Fu; Cao, Xin; Qian, Biao; Song, Peipei
Abstract: Distributed Arithmetic (DA) is a classic technique for the hardware realization of digital filters. We present a novel parallel arithmetic operation to overcome two drawbacks in existing DA and DA-based methods: 1) the throughput is difficult to improve and 2) hardware resource consumption increases exponentially with the length of filter order. The fundamental difference between the proposed and existing methods is that the proposed method factors the filter coefficients to find several simple basic operations, which can circumvent the inherent bit-serial nature of DA methods and achieve the whole operation in one clock cycle. Additionally, the number of possible basic operations increases linearly with the length of filter order, which means we can relieve the exponentially increasing hardware resource consumption. The proposed method is evaluated through two experiments, and the results demonstrate that the proposed technique outperforms existing DA and DA-based methods in terms of throughput and resource consumption.